Anatomy and histochemistry of Manihot caerulescens Pohl (Euphorbiaceae) Leaf anatomy of Manihot caerulescens - Silva, Lucimara Reis de Oliveira [UNESP]; Martins, Fabiano Machado; Martins, Márcio Lacerda Lopes (Wiley, 2019)
This study aimed to analyze the leaf anatomy of Manihot caerulescens, with emphasis on the ontogeny and secretion composition of the laticifers. Leaf samples were submitted the usual techniques in plant anatomy and histochemical tests to identify the main classes of secondary metabolites. The analyzes were performed using light and scanning electron microscopy. The leaves have a single layered epidermis coated by a uniform cuticle. The epidermal cells are elongated and papillose on the leaf abaxial surface of leaves. The mesophyll is isobilateral and the vascular bundle of the midrib is collateral. The laticifers are originated from ground meristem and procambium, and are of articulated anastomosing type. Besides the laticifers, two types of idioblasts were found: the secretory idioblasts, with a dense content, and the calcium oxalate druses idioblasts. Histochemical tests revealed different classes of chemicals for both secretory idioblasts and laticifers. In idioblasts, a positive reaction was detected for the general phenolic compounds, proteins, total polysaccharides and tannins. The laticifers reacted positively to total lipids and acids, essences, total polysaccharides and rubber. The individuals analyzed here are from caatinga and their leaf anatomical structure showed to be different from that described for the same species growing in the cerrado.
Keywords: caatinga; idioblast; laticifer; leaves; secondary metabolism